OUTCOME OF PATIENTS WITH DIFFUSE LARGE B-CELL LYMPHOMA RELAPSING AFTER AUTOLOGOUS TRANSPLANT BEFORE AVAILABILITY OF CAR-T CELL TREATMENT - Ulrike Bacher; Stefanie von Matt; Yara Banz; Behrouz Mansouri Taleghani; Urban Novak; Thomas Pabst (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Introduction: Autologous stem cell transplantation (ASCT) following high-dose chemotherapy is applied for patients with relapsed/refractory (r/r) DLBCL. However, prognosis of relapsing DLBCL post-ASCT remained poor until the availability of CAR-T cell treatment. To appreciate this development, understanding the outcome of these patients in the pre-CAR-T era is essential.